2020
DOI: 10.1007/s11357-020-00164-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular unit dysregulation, white matter disease, and executive dysfunction: the shared triad of vascular cognitive impairment and Alzheimer disease

Abstract: Executive dysfunction is the most important predictor for loss of independence in dementia. As executive function involves the coordination of distributed cerebral functions, executive function requires healthy white matter. However, white matter is highly vulnerable to cerebrovascular insults, with executive dysfunction being a core feature of vascular cognitive impairment (VCI). At the same time, cerebrovascular pathology, white matter disease, and executive dysfunction are all increasingly recognized as fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 229 publications
(396 reference statements)
1
50
0
1
Order By: Relevance
“…Consistent with our results, studies have reported that patients with lacunar infarction had impaired CA in bilateral hemispheres 32,33 . The possible mechanism behind this phenomenon is neurovascular unit dysfunction in small vessel disease, 34 which is consistent with the finding that VLF phase shift is the optimal CA index for predicting poststroke cognitive impairment. Patients with AD were found to have normal CA, 35 which is consistent with the lack of association between CA and lobar microbleeds observed in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our results, studies have reported that patients with lacunar infarction had impaired CA in bilateral hemispheres 32,33 . The possible mechanism behind this phenomenon is neurovascular unit dysfunction in small vessel disease, 34 which is consistent with the finding that VLF phase shift is the optimal CA index for predicting poststroke cognitive impairment. Patients with AD were found to have normal CA, 35 which is consistent with the lack of association between CA and lobar microbleeds observed in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Both brain glucose and oxygen could be measured with PET dynamic activation as a potential method to highlight patients for specific metabolic interventions 11 . Further, neurovascular coupling to a variety of activation paradigms may be tested in MCI and AD patients to understand the translation of these concepts to the clinical condition 28 . These could be tested with clinical activation including sensory or direct nerve stimulation.…”
Section: Narrativementioning
confidence: 99%
“…However, the comprehension of brain vascular pathophysiology requires the understanding of their molecular basis. To achieve this goal, both the multifactorial nature of these diseases and the central concept of neurovascular unity (NVU) should be considered ( Takahashi, 2020 ; Levit et al, 2020 ). However, the complex biology behind the neurovascular brain pathology is still full of open questions.…”
Section: Introductionmentioning
confidence: 99%